Whole Plastome Sequencing Within Silene Section Psammophilae Reveals Mainland Hybridization and Divergence With the Balearic Island Populations - del Valle, José Carlos; Casimiro-Soriguer, Inés; Buide, Mᵃ Luisa; Narbona, Eduardo; Whittall, Justen B. (Frontiers in Plant Science, 2019)
Reconstructing the phylogenetic relationships within Caryophyllaceae Tribe Sileneae has been obscured by hybridization and incomplete lineage sorting. Silene is the largest genus in the Caryophyllaceae and unraveling its evolutionary history has been particularly challenging. In order to infer the phylogenetic relationships among the five species in Silene section Psammophilae, we have performed a genome skimming approach to acquire the complete plastid genome (cpDNA), nuclear ribosomal cistron (nrDNA) and partial mitochondrial genome (mtDNA). We have included 26 populations, representing the range of each species’ distribution. This section includes five morphologically similar species endemic to the Iberian Peninsula and Balearic Islands (Ibiza and Formentera), yet some of them occupy distinct edaphic habitats (e.g. maritime sands, calcareous sandstones). In addition to phylogeographic analyses, genetic structuring using the chloroplast dataset was inferred with Discriminant Analysis of Principal Components (DAPC), AMOVA and a partial Mantel test. Reference-guided assembly of 50-bp single-end and 250-bp paired-end Illumina reads produced the nearly complete cpDNA genome (154 kbp), partial mtDNA genome (from 81 to 114 kbp), and the nrDNA cistron (6.4 kbp). Selected variable regions of the cpDNA and mtDNA assemblies were confirmed by Sanger sequencing. Phylogenetic analyses of the mainland populations reveal incongruence among the three genomes. None of the three datasets produced relationships consistent with taxonomy, or geography. In contrast, Silene cambessedesii, present in the Balearic Islands, is the only species that forms a strongly supported monophyletic clade in the cpDNA genome and is strongly differentiated with respect to the remaining taxa of the Iberian Peninsula. These results contrast with those obtained for mainland populations. Across the entire analysis, only one well-supported mainland clade of S. littorea and S. stockenii emerges from the southern region of the Iberian Peninsula. DAPC and AMOVA results suggest the absence of genetic structure among mainland populations of Silene Section Psammophilae, whereas partial Mantel test discarded spatial correlation of genetic differentiation. The widespread incongruence between morphology-based taxonomic boundaries and phylogeography suggests a history of interspecific hybridization, in which only a substantial geographic barrier, like isolation by the Mediterranean Sea, was sufficient to create and maintain species boundaries in Silene Section Psammophilae.